Long-term Home Mechanical Ventilation of Children in İstanbul - Mürüvvet Yanaz; Füsun Ünal; Evrim Hepkaya; Hakan Yazan; Sinem Can Oksay; Ebru Köstereli; Cansu Yılmaz Yeğit; Azer Kılıç Başkan; Zeynep Reyhan Onay; Aynur Gulieva; Aslınur Soyyiğit; Mine Kalyoncu; et al. (Thoracic Research and Practice)
OBJECTIVE: The aims of this multi-center study were to describe the characteristics of children receiving long-term home mechanical ventilation (HMV) in İstanbul and to compare the patients receiving non-invasive and invasive ventilation. MATERIAL AND METHODS: This cross-sectional multicenter study included all children receiving long-term HMV followed by admission to six tertiary hospitals. The data were collected between May 2020 and May 2021. Demographic data and data regarding HMV were collected from the patient charts. RESULTS: The study included 416 participants. The most common diagnoses were neuromuscular (35.1%) and neurological diseases (25.7%). Among the patients, 49.5% (n = 206) received non-invasive ventilation (NIV), whereas 50.5% (n = 210) received invasive ventilation. The median age at initiation was significantly younger in the invasive ventilation group than in the NIV group (10 vs. 41 months, P < 0.001). Most subjects in the NIV group (81.1%) received ventilation support only during sleep, whereas most subjects in the invasive ventilation group (55.7%) received continuous ventilator support (P < 0.001). In addition to ventilation support, 41.9% of the subjects in the invasive ventilation group and 28.6% in the NIV group received oxygen supplementation (P = 0.002). Within the last year, 59.1% (n = 246) of the subjects were hospitalized. The risk factors for hospitalization were invasive ventilation, continuous ventilatory support, oxygen supplementation, tube feeding, and swallowing dysfunction (P = 0.002, 0.009, <0.001, <0.001 and <0.001 respectively). CONCLUSION: Despite the increasing use of NIV in most studies, half of the study population received invasive ventilation. Patients receiving invasive ventilation were more likely to require continuous ventilator support and oxygen supplementation and were at increased risk of hospitalization.